2008
DOI: 10.1038/modpathol.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of XIAP and p63 in adenomatous hyperplasia, atypical adenomatous hyperplasia, bronchioloalveolar carcinoma and well-differentiated adenocarcinoma

Abstract: The critical distinction of bronchioloalveolar carcinoma (BAC), well-differentiated adenocarcinoma (WDAC) of lung, adenomatous hyperplasia (AH) and atypical adenomatous hyperplasia (AAH), is based on morphological criteria alone, and is therefore potentially subjective. We examined expression of two markers, X-linked inhibitor of apoptosis protein (XIAP), the most potent of the inhibitor of apoptosis protein (IAP) family, and p63, a marker of bronchial reserve cells (BRC) and squamous cells, in these entities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We hypothesize an origin from the basal reserve cells of the TRU that show positive immunostaining for TTF1 and p63, overlapping with the results obtained in our 10 cases of PD-NSCLC. This hypothesis has been previously suggested by Wu et al [12], limited to previously called "brochiolo-alveolar carcinomas" and "well-differentiated adenocarcinomas (WD-ADC)", but not for PD-NSCLC. Moreover, TTF-1 was not assessed in their study.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We hypothesize an origin from the basal reserve cells of the TRU that show positive immunostaining for TTF1 and p63, overlapping with the results obtained in our 10 cases of PD-NSCLC. This hypothesis has been previously suggested by Wu et al [12], limited to previously called "brochiolo-alveolar carcinomas" and "well-differentiated adenocarcinomas (WD-ADC)", but not for PD-NSCLC. Moreover, TTF-1 was not assessed in their study.…”
Section: Discussionmentioning
confidence: 73%
“…In lung ADCs, positive immunostaining for p63 is rare; when present, it has been reported as weak and focal [5,[9][10][11][12][13]. Only in 5.5% of cases has coexpression of both TTF-1 and p63 in the same cellular elements been reported [10][11][12]14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To find differentially expressed genes between lung cancer subtypes, we used only tumor samples of different subtypes as sample groups. Because of the small sample size and similar histology27 of AC and BC samples we used these in analyses as one group. We identified 112 genes which were up-regulated and 101 genes which were down-regulated in AC/BC compared to the SCC (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…XIAP, cIAP1 and cIAP2 are expressed in normal tissue, but numerous studies have indicated upregulation of these proteins in cancer cell lines and tissues [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Although some studies have found a correlation between these IAPs expression levels and chemoresistance, poor prognosis or cancer progression [38,41,[52][53][54][55][56][57][58][59][60], others have not [61][62][63].…”
Section: The Role Of Iaps In Cancermentioning
confidence: 98%